(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2013)
A new macrocyclic diarylheptanoid, 1-desmethylgaruganin III (1) was isolated from a dichloromethane extract of the stem bark of Garuga pinnata. The structure of the compound was elucidated by high field NMR studies as well as comparison with spectral data of related compounds. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14575 Dhaka Univ. J. Pharm. Sci. 11(2): 165-167, 2012 (December)